Introduction to dossier. Economic elites and political power in Latin America - Ruiz-Acosta, Miguel; Báez-Valencia, Jonathan; Hurtado-Arroba, Edison (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2023)
Introduction to dossier. Economic elites and political power in Latin America